Comparison of the mechanical properties of flax and glass fiber composite materials - (:unkn) unknown (JOURNAL VIBROENGINEERING, 2012)
In this paper, the comparison of static and dynamic properties of flax and glass fiber composite materials is presented. For this comparison, dynamic and quasi-static experimental studies were carried out. As a dynamic test, vibration tests were fulfilled using the Oberst apparatus and the tensile test was fulfilled by a quasi-static test. The vibration tests were carried out under different temperatures by using temperature and climatic test cabinets. Flax and glass fibers were used as reinforcements, and polyester resin was used as a matrix to make up the composite specimens. According to the obtained results, the strength of flax fiber composite is lower than the glass fiber under tensile loading, but approximately the same under vibration excitation. On the other hand, damping characteristics of flax fiber composite is higher than glass fiber composite materials. These results demonstrated that natural fiber materials can be used instead of chemical materials for vibration absorption due to their high damping.
Keywords: flax fiber; glass fiber; Young's modulus; vibration; damping; TENSILE BEHAVIOR; LOCATION; STEM